2005
DOI: 10.1073/pnas.0409829102
|View full text |Cite
|
Sign up to set email alerts
|

Selective modification of alternative splicing by indole derivatives that target serine-arginine-rich protein splicing factors

Abstract: The prevalence of alternative splicing as a target for alterations leading to human genetic disorders makes it highly relevant for therapy. Here we have used in vitro splicing reactions with different splicing reporter constructs to screen 4,000 chemical compounds for their ability to selectively inhibit spliceosome assembly and splicing. We discovered indole derivatives as potent inhibitors of the splicing reaction. Importantly, compounds of this family specifically inhibit exonic splicing enhancer (ESE)-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 39 publications
2
106
0
2
Order By: Relevance
“…Recent studies have shown that the relative concentrations of SR proteins are of paramount importance for production of sufficient quantities of the various HIV-1 mRNAs (16). SR proteins have also been shown to be potential targets for novel therapy against HIV-1 infection (28). It is therefore of interest to identify the cellular splicing factors that regulate HIV-1 mRNA splicing.…”
mentioning
confidence: 99%
“…Recent studies have shown that the relative concentrations of SR proteins are of paramount importance for production of sufficient quantities of the various HIV-1 mRNAs (16). SR proteins have also been shown to be potential targets for novel therapy against HIV-1 infection (28). It is therefore of interest to identify the cellular splicing factors that regulate HIV-1 mRNA splicing.…”
mentioning
confidence: 99%
“…Focusing on splicing correction strategies for SMA, certain drugs have been shown to modulate alternative splicing decisions, 112,113 but in general their specificity is low and side effects are therefore a major concern. Concerning SMA, beneficial splicing effects were reported for aclarubicine, 114 but the drug proved to be quite toxic.…”
mentioning
confidence: 99%
“…There are several kinases, for example, Clk/Sty, SRPK1, SRPK2 and topoisomerase I that are known to phosphorylate SR proteins. Several compounds have been reported that target these kinases, for example, diospyrin (Tazi et al, 2005a), indole derivatives (Soret et al, 2005) and indolocarbazole (NB506; Pilch et al, 2001), inhibit the kinase activity of topoisomerase I. Similarly, a benzothiazole compound displayed clear inhibitory effects on the activity of Clk1/Sty (Muraki et al, 2004).…”
Section: Targeting Of Splice Modulatorsmentioning
confidence: 99%